Transportation competitiveness in the context of international trade - Zamora Torres, América I. (2013)
Currently almost all international shipments need to use more than one type of transportation from point of origin to final destination. Each one of the types of global transport has played an essential role in facilitating geographic diversification. In this paper we evaluate through Principal Component Analysis methodology the international transport competitiveness considering the most important variables that affect this sector and the economic performance of these variables on transportation, analyzing the structure of the international transport system of twenty-nine countries including seven Latin America´s countries. The results shown in the competitiveness index of international transportation indicate that the most competitive countries in international transport according to the variables assessed are: U.S. Hong Kong, Singapore, China, Sweden, Spain, Japan, Belgium, Denmark and Canada. Highlighting that, the countries of Latin America with the highest scores in this category are Brazil, followed by Panama, Chile and Costa Rica.